THE ABUSE OF AUTHORSHIP IN THE BIOMEDICAL LITERATURE - Jaime A. Teixeira da Silva (Central Asian Journal of Medical Hypotheses and Ethics, 2023)
The ‘publish or perish’ culture has induced an unhealthy aspect of academic publishing in the biomedical sciences, namely of illegitimate authorship. Such a position can be obtained when an authorship slot is offered as a gift (e.g., to a sponsor, or researcher in a senior position), without their intellectual or scientific participation, or it can be hidden (ghost authorship), in which the paper (or parts thereof) is written by a third party (individual, or company). In a more industrialized setting, ghost authorship takes place via the sale of papers using “paper mills”, including of specific author slots (i.e., positions in a line of authors). While author-based persistent identifiers like ORCID, or authorship attribution schemes like CRediT, sound noble and offer some form of validation, those systems still operate on a culture of blind trust (in submitting authors). This paper debates a few of the authorship-related issues currently plaguing biomedical journals.